2023
DOI: 10.3171/2023.5.focus23227
|View full text |Cite
|
Sign up to set email alerts
|

MR-guided focused ultrasound–induced blood-brain barrier opening for brain metastasis: a review

Giovanni Grasso,
Fabio Torregrossa,
Manfredi Noto
et al.

Abstract: Although the therapeutic armamentarium for brain metastases (BMs) has been expanded from innovative surgical techniques and radiotherapy to include targeted therapies and immunotherapy, the prognosis of BMs remains poor. Despite the proven efficacy of numerous compounds in preclinical studies, the limited penetration of promising therapeutic agents across the blood-brain barrier (BBB) remains an unaddressed issue. Recently, low-intensity magnetic resonance–guided focused ultrasound (MRgFUS) in combination with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Oscillations induce stretching, acoustic streaming, and shear forces on the vasculature, which can affect the permeability of tight junctions and the function of efflux transporter proteins [ 18 , 19 ]. There are several varieties of microbubbles available on the market, and an ideal agent is one which induces stable cavitation, decreases the nearby production of P-glycoprotein, and results in the formation of caveolae (invaginations in the plasma membrane) [ 20 , 21 ]. A study comparing three commercially available types of microbubbles found all three to perform equivalently in terms of degree and persistence of BBB permeabilization [ 22 ]; based on the size and half-life of the microbubble, ultrasound parameters (power and duration) can be varied slightly to optimize MB performance [ 22 ].…”
Section: Mechanism Of Ultrasonic Bbb Openingmentioning
confidence: 99%
See 1 more Smart Citation
“…Oscillations induce stretching, acoustic streaming, and shear forces on the vasculature, which can affect the permeability of tight junctions and the function of efflux transporter proteins [ 18 , 19 ]. There are several varieties of microbubbles available on the market, and an ideal agent is one which induces stable cavitation, decreases the nearby production of P-glycoprotein, and results in the formation of caveolae (invaginations in the plasma membrane) [ 20 , 21 ]. A study comparing three commercially available types of microbubbles found all three to perform equivalently in terms of degree and persistence of BBB permeabilization [ 22 ]; based on the size and half-life of the microbubble, ultrasound parameters (power and duration) can be varied slightly to optimize MB performance [ 22 ].…”
Section: Mechanism Of Ultrasonic Bbb Openingmentioning
confidence: 99%
“…Building on these experiences, a multi-center study to examine the safety of the procedure in patients with diffuse midline glioma is currently underway (NCT05615623). An ongoing multicenter study is looking to compare the MRgFUS-enhanced delivery of pembrolizumab, an immune checkpoint inhibitor, to non-enhanced delivery in patients with non-small cell lung cancer with brain metastases (NCT05317858) [ 21 ].…”
Section: Neuro-oncologymentioning
confidence: 99%
“…When stimulated by LIFU, MBs expand or contract, opening the tight junctions of the BBB/BTB and delivering drugs into brain tumors. 153 , 155 Several studies have reported that some drugs (eg, trastuzumab, 156 bevacizumab, 157 carboplatin, 158 , 159 temozolomide, 160 methotrexate, 161 and doxorubicin 162 ) can be delivered through the BTB using LIFU. Notably, LIFU has been demonstrated to have no significant side effects, and the pores or “windows” it forms on the BBB close within 6–8 h, preventing prolonged exposure and potential damage to neurons.…”
Section: Targeted Delivery Based On Mnpsmentioning
confidence: 99%